Genome assemblies for Chromidotilapia guntheri (Teleostei: Cichlidae) identify a novel candidate gene for vertebrate sex determination, RIN3 - Behrens, Kristen A.; Koblmüller, Stephan; Kocher, Thomas D. (Frontiers in Genetics, 2024)
Advances in genome sequencing have greatly accelerated the identification of sex chromosomes in a variety of species. Many of these species have experienced structural rearrangements that reduce recombination between the sex chromosomes, allowing the accumulation of sequence differences over many megabases. Identification of the genes that are responsible for sex determination within these sometimes large regions has proved difficult. Here, we identify an XY sex chromosome system on LG19 in the West African cichlid fish Chromidotilapia guntheri in which the region of differentiation extends over less than 400kb. We develop high-quality male and female genome assemblies for this species, which confirm the absence of structural variants, and which facilitate the annotation of genes in the region. The peak of differentiation lies within rin3, which has experienced several debilitating mutations on the Y chromosome. We suggest two hypotheses about how these mutations might disrupt endocytosis, leading to Mendelian effects on sexual development.